Gestational Age of Delivery in Pregnancies Complicated by Chronic Hypertension. Issue 6 (June 2016) - Harper, Lorie M.; Biggio, Joseph R.; Anderson, Sarah; Tita, Alan T.N.
Abstract : OBJECTIVE: To identify the gestational age of planned delivery in pregnancies complicated by chronic hypertension that minimizes the risk of perinatal death and severe adverse events. METHODS: This was a retrospective cohort study of all singletons complicated by hypertension. Detailed patient-level information was collected by chart review, including indication for delivery. Planned delivery at 36–36 6/7, 37–37 6/7, 38–38 6/7, and 39–39 6/7 weeks of gestation was compared with expectant management beyond each respective gestational age. Patients were excluded for fetal anomalies, inaccurate dating, and major medical problems other than hypertension, diabetes, or renal disease. The primary outcome was a composite of stillbirth, neonatal death, assisted ventilation, cord pH less than 7.0, 5-minute Apgar score of 3 or less, and neonatal seizures. Secondary outcomes were preeclampsia, severe preeclampsia, primary cesarean delivery, and neonatal length of stay greater than 5 days. Groups were compared using Student's t test and χ 2 tests. RESULTS: Six hundred eighty-three women with hypertension reached 36 weeks of gestation. Patients with planned delivery at less than 39 weeks of gestation were more likely to have baseline renal disease. Before 37 weeks of gestation, planned delivery was associated with a statistically significant increase in the primary composite adverse neonatal outcome (10.0% compared with 2.6%, P =.04); after 38 weeks of gestation, expectant management was associated with a nonstatistically significant increase in the primary composite outcome (0% compared with 2.3%, P =.40). Expectant management beyond 39 weeks of gestation was associated with a statistically significant increase in severe preeclampsia (0% compared with 10.3%, P =.001). CONCLUSION: Expectant management beyond 39 weeks of gestation was associated with increasing incidence of severe preeclampsia; planned delivery before 37 weeks of gestation was associated with an increase in adverse neonatal outcomes. Further well-powered studies are needed to delineate the optimal gestational age of delivery. Abstract : Perinatal morbidity and mortality in pregnancies complicated by chronic hypertension reaches a nadir after 38 weeks of gestation, although the optimum gestational age for delivery remains uncertain.